Medical Education in Naples, Italy, at the Time of SARS-CoV-2 - Gianluca Pagano; Gaetano Luglio (International Journal of Medical Students, 2020)
SARS-CoV-2 pandemic dramatically changed our daytime routine. Our university world was deeply affected by this emergency situation and had to guarantee the teaching activity with online lessons and exams. While it is true that even in non-emergency conditions online teching is an integral part of many universities, the same cannot be said for graduation ceremonies. And what about students' clinical practice and research activity? In the present article, we will discuss about the experiences of a final-year medical student and of a young assistant professor of Surgery.